Mentilin (Tarsius bancanus) The Smallest Primate at The Taman Kehati Pelawan, Central Bangka - Ratna Sari Hasibuan; Agus Seftian Pracahyo; Miftahul Ihsan (JURNAL SAINS NATURAL, 2023)
One of the primitive primates and the smallest nocturnal is Mentilin or Tarsius. Mentilin (Tarsius bancanus) is an endemic animal scattered on the islands of Sulawesi, Kalimantan, Bangka and Belitung. Mentilins are protected animals and are listed in CITES Appendix II. The existence of forest degradation on Bangka Island due to illegal logging, conversion of land to plantation land, and illegal tin mining by the community and companies on a large scale has caused the mentilin’s habitat to decrease. This study's purpose was to determine the total population of mentilin and determine the habitat of mentilin in the Pelawan Forest. The method used is line transect and vegetation analysis. The results of this study were a total of 6 Mentilin found from two groups and a tree-level diversity of 1.67; Pole 2.48; 3.41 saplings and 3.40 seedlings. Mentilin density in Pelawan Forest is 21.4 mentilin per km2, with a sex ratio of 1:2 Dominated by Pelawan Plants.